2022
DOI: 10.26675/jabe.v6i2.21265
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Internal Audit Reporting on Public Sector in Sri Lanka

Abstract: The main purpose of this study is to identify significant factors affecting the effectiveness of internal audit reporting in public sector in the Northern Province, Sri Lanka. This study used the primary data collected from the heads of departments, divisions, and internal auditors in public sector in the Northern Province of Sri Lanka through the developed questionnaire. The regression analysis confirmed that the tested factors significantly affected the effectiveness of internal audit reporting, especially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…For example, audit standards require an auditor's intermittent report, which provides reasonable assurance that no material misstatement exists in an organisation's financial statement and financial report as a whole (Backof, 2014). The greater the internal auditor independence of internal auditor accountability and transparency, the greater the effectiveness of internal audit reporting (Anojan, 2022). Agbenyo and Cobblah (2018) found that a unit increase in collection performance results in an improvement in the quality of financial reporting.…”
Section: 23internal Reporting Systemmentioning
confidence: 99%
“…For example, audit standards require an auditor's intermittent report, which provides reasonable assurance that no material misstatement exists in an organisation's financial statement and financial report as a whole (Backof, 2014). The greater the internal auditor independence of internal auditor accountability and transparency, the greater the effectiveness of internal audit reporting (Anojan, 2022). Agbenyo and Cobblah (2018) found that a unit increase in collection performance results in an improvement in the quality of financial reporting.…”
Section: 23internal Reporting Systemmentioning
confidence: 99%
“…Furthermore, still exist challenges and expectations from internal auditors higher to operate daily activities at their level best. So, the basic attributes of internal audit are not designed (Anojan 2022).…”
Section: Introductionmentioning
confidence: 99%